2012
DOI: 10.1002/jmri.23814
|View full text |Cite
|
Sign up to set email alerts
|

Auto‐Threshold quantification of late gadolinium enhancement in patients with acute heart disease

Abstract: Automatic thresholding using OAT may serve as an accurate and reproducible method to quantify irreversible myocardial injury in acute heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 27 publications
4
42
2
Order By: Relevance
“…The good performance of the ATA in the detection of LGE matched the results of a recent study [13] that identified the Otsu algorithm [14] as the best method for fully automated thresholding. Ridler's algorithm that was used in the present study, is very similar to Otsu's algorithm.…”
Section: Discussionsupporting
confidence: 77%
“…The good performance of the ATA in the detection of LGE matched the results of a recent study [13] that identified the Otsu algorithm [14] as the best method for fully automated thresholding. Ridler's algorithm that was used in the present study, is very similar to Otsu's algorithm.…”
Section: Discussionsupporting
confidence: 77%
“…[26,27] There is no histological validation in humans and hence no ‘gold standard’ quantification. We thus used manual assessment as has been used previously [6,12], however derived from the mean of repeated analyses by three experienced CMR cardiologists to increase the robustness of our reference standard.…”
Section: Discussionmentioning
confidence: 99%
“…The same signal intensity threshold was set for all slices on 5/6/7/8 SD and FWHM thresholding. OAT automatically calculates a unique signal intensity threshold for each slice by dividing the greyscale signal intensity histogram in each slice into 2 groups (enhanced, normal) based on the signal intensity threshold giving the least intraclass variance (lowest sum of variances) and thus most homogeneity of signal intensities within each group (Figure 2) [11,12]. The only user input, and thus potential sources of variation are the endocardial and epicardial contours, and manual correction of noise artefact.…”
Section: Methodsmentioning
confidence: 99%
“…The Ridler algorithm is an iterative version of the Otsu method, which was demonstrated to be accurate and reproducible for defining infarct size in patients with acute myocardial infarction (16). On the basis of the wave-front theory, areas of microvascular obstruction (with no reflow) were defined as subthreshold areas located under LGE areas (in the epicardial-endocardial direction) and were automatically detected with a radial search algorithm.…”
Section: Mr Imaging Protocolmentioning
confidence: 99%